IMPLEMENTASI RESTFUL API PADA APLIKASI SALES MANAGEMENT DENGAN LARAVEL 11 DAN SANCTUM DI PT. POWERPOS GLOBAL NETWORK - Agun Firmansyah; Reny Wahyuning Astuti (FORTECH (Journal of Information Technology), 2026)
This research focuses on the implementation of a RESTful API for a sales management application at PT PowerPOS Global Network, a startup developing a cloud-based Point-of-Sale application. The background of the problem shows significant inefficiencies due to reliance on manual processes (Microsoft Excel and WhatsApp) in managing the sales team, which leads to information fragmentation and a lack of real-time visibility. The proposed solution is the development of a RESTful API using the Laravel 11 framework and Sanctum for authentication. This API is designed to integrate various system components, enabling automatic and real-time master data management, attendance monitoring, assignment distribution, and sales performance reporting. This implementation aims to improve operational effectiveness, support faster and more accurate strategic decision-making, and build a robust and scalable digital ecosystem for PT PowerPOS Global Network.